ANALISIS SENYAWA SITRULIN EKSTRAK AIR DAN EKSTRAK ETANOL DAGING DAN KULIT BUAH BLEWAH (Cucumis melo L.) - Antonius Padua Ratu; Herson Cahaya Himawan; M. Rio Radhi (Jurnal Farmamedika (Pharmamedika Journal), 2016)
Data from the United States Department of Agriculture (USDA) National Nutrient database, that cantaloupe contains amino acids of 0.8 grams / 100 grams. One of the amino acids found in cantaloupe is citrulline which can contribute to oxidative stress as a free radical scavenger. The purpose of this study was to obtain the optimal content of citrulline compound in the flesh and skin of blewah to the method of extraction. The method used is the maceration method with ethanol and water solvent, digestion and dekokta method only with water solvent. Quantitatively, sitrulin is obtained by acid hydrolysis and is reacted with a specific reagent which is 3% diacetyl monoxime in a hot temperature. The reading of the result using the maximum wavelength spectrophotometer is 488 nm. The highest content of citrulline compound was shown by decocta method of aquatic leather water extract (7.72 g / 100g). The citrulline content was significantly different (P <0.05) on the difference in other extraction methods.